The complete mitochondrial genome of Sanghuangporus sanghuang (Hymenochaetaceae, Basidiomycota). Issue 1 (2nd January 2018) - Han, Jae-Gu; Oh, Junsang; Jo, Jong Won; Kim, Chang Sun; Kwag, Young-Nam; Han, Sang-Kuk; Sung, Gi-Ho
Abstract: Sanghuang is a polypore mushroom, which has been widely used in oriental medicine. Since recent molecular phylogenetic studies elucidated its species delimitation, Sanghaungporus sanghuang became the official name of this fungus. In this study, the complete sequence of the mitochondrial DNA of S. sanghuang was determined. The whole genome was 112, 060 bp containing 14 proteins, 2 ribosomal RNA subunits, and 45 transfer RNAs. The overall GC content of the genome was 23.21%. A neighbour-joining tree based on atp6 sequence data showed its close relationship with the species of Ganoderma and Trametes .